Finding the contextually appropriate: student reflection as a dialogic reflective practice tool. Issue 3 (3rd May 2020) - Unlu, Zuleyha
ABSTRACT: This paper focuses on Reflective practice (RP hereafter), the learning and teaching features of Generation Z, and the issue of large classrooms in ELT. Facing the challenge of teaching speaking to the Generation Z students at a large higher education classroom, the researcher designed her course through student reflections, an under-utilized RP tool. In the reflections, students evaluated their large speaking class by focusing on four areas: their perceptions of the class, suggestions for diminishing the impact of class size, and suggestions for their peers for individual study to improve their speaking with and without online resources despite the disadvantage of being in a crowded class. Once the data was gathered through student reflections and the supplementary notes, the researcher analysed the data using grounded theory coding procedures. Based on the findings, the researcher designed the course of the next semester. At the end, the researcher conducted reflection on the reflection both individually and with students. The findings and the complete reflection procedure indicated that the student reflection was a powerful tool for course design in a large classroom as well as addressing the learning requirements of the learners, Generation Z in this example.